Avaliação da problemática da acessibilidade e mobilidade às oportunidades de trabalho em Belo Horizonte - André Augusto Cunha Libânio (2020)
The objective of this dissertation was to understand the problem of accessibility to work opportunities and its relationship with mobility in the city of Belo Horizonte. To this end, the method developed by Garcia et al. (2018) was applied to understand, at a strategic level, the unequal and inequitable distribution problems of accessibility and mobility, based on techniques of spatial analysis and ethical theories of social justice. The applied metho comprises the characterization and diagnosis of accessibility and mobility problems based on the relationships between contributing factors to the conformation of these problems and their characteristics. For this purpose, the selected indicators were submitted to exploratory analysis, considering non-spatial and spatial approaches. As a result of the characterization phase, it was verified that Belo Horizonte presents unequal and inequitable distributions of accessibility and mobility to work opportunities. Unlike accessibilitywhich presents higher levels in the central region of the city, , mobility presents a very dispersed pattern of spatial distribution. In the diagnostic phase, problem areas were delimited from the point of view of unequal distribution, based on sufficiency parameters for each transportation mode. From the perspective of inequitable distribution, the problematic zones were superimposed on the previously defined regions of social interest, identifying critical areas for which investments should be prioritized in order to achieve more equitable levels of accessibility and mobility. Finally, analyses of the relationships between accessibility and mobility and the urban attributes behind these problems were carried out. The results indicated that spatial models were better suited than non-spatial models to the phenomena under analysis. The inclusion of the spatial approach for explanatory models that contribute to accessibility and mobility understanding reinforces the importance of considering spatial aspects in this kind of urban analysis, since many studies in this research field limit themselves to considering non-spatial regression models, disregarding the spatial dependence.